Nature, Culture, and War in the Writings of Step’annos Orbelian - Foletti, Ivan; Kovářová, Michaela (Eikón / Imago, 2026)
This article reflects on how the transformation of natural sites into cultural spaces was perceived in medieval Armenia, as analysed in The History of the State of Sisakan, written by the bishop and historian Stepanos Orbelian (c. 1250–1304). Orbelian's text opens with the familiar theme of a natural environment being transformed from a desert into a paradise, and describes how monastic colonisation turned a wild landscape into a prosperous cultural and fertile place. Art and culture are presented as instruments that bring the environment closer to God's will: thanks to the monastic presence, the region was protected from floods and bad weather. However, human action cannot be seen as positive alone: various invasions by foreign forces should be seen as elements of rupture, damaging nature and culture in order to satisfy diabolical greed. By analysing textual data and architectural heritage, this text explores some of the questions raised within Ecocritical Art History, attempting to understand the issue of the 'exploitation' of natural sites in the past.